Systematic review of AAC-based communication intervention in children with cerebral palsy. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
INTRODUCTION:Communication is a fundamental tool for living together in society, which is why the importance of augmentative and alternative communication in the intervention of people who present alterations at the level of speech or languages, as is often the case in children with cerebral palsy. METHODS:This study was carried out under the systematic review methodology where search predictors such as cerebral palsy and augmentative and alternative communication were used. RESULTS:The most commonly used intervention strategies today are mobile applications, followed by CAA dashboards. ANALYSIS AND DISCUSSION:The use of AAC improves communication in children with cerebral palsy, although there may be limitations in its use. CONCLUSIONS:This research served to analyze the strategies most used for intervention in this population and to encourage more communication professionals to carry out more studies on the use of AAC in children with CP
Keywords: cerebral palsy; augmentative and alternative communication; communication technology; supplemental communication